Conservation of library materials : a seminar, 1985 - Das Gupta, Kalpana; National Library (India) (Calcutta : National Library, 1971)
Contributed seminar papers.
Includes bibliographical references.
"Conservation of Library materials, a select bibliography": p. 122-224.
Keywords: Library materials -- Conservation and restoration -- India -- Congresses